2012
DOI: 10.2514/1.j051192
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Shape Optimization of Wings Using a Parallel Newton-Krylov Approach

Abstract: A Newton-Krylov algorithm for aerodynamic shape optimization in three dimensions is presented for both singlepoint and multipoint optimization. An inexact Newton method is used to solve the Euler equations, a discrete adjoint method is used to compute the gradient, and an optimizer based on a quasi-Newton method is used to find the optimal geometry. The flexible generalized minimal residual method is used with approximate Schur preconditioning to solve both the flow equation and the adjoint equation. The wing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Applications of CFD-based ASO to wing design have, up until recently, largely focused on the Euler equations [21][22][23][24][25][26][27][28]. Contrary to circulation-distribution and panel methods, the Euler equations do not require the user to prescribe the starting location and shape of the wake.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of CFD-based ASO to wing design have, up until recently, largely focused on the Euler equations [21][22][23][24][25][26][27][28]. Contrary to circulation-distribution and panel methods, the Euler equations do not require the user to prescribe the starting location and shape of the wake.…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques have been developed by Zingg and colleagues (Hicken and Zingg 2010;Leung and Zingg 2012), and have shown that these types of methods can be flexible enough to allow the moulding of a sphere into an aircraftlike shape under certain optimization conditions (Gagnon and Zingg 2012). Further work has been performed by Martins and others (Mader and Martins 2013;Lyu and Martins 2014) who showed results for blended-wing-body optimizations, and Yamazaki et al (2010) who further reduced the number of design variables by considering the direct manipulation method for wing optimization.…”
Section: Shape Parameterizationmentioning
confidence: 99%
“…30 Further implementations of these types of methods have a http://www.optimalsolutions.us/ (2008) also been adopted by Zingg and colleagues. [31][32][33] Reviews of a range of parameterization methods have also been presented, and the reader is guided towards the work of Samareh 34, 35 and Nadarajah. 36,37 An effective parameterization must be i) flexible enough to allow sufficient design space investigation, ii) robust enough to be applicable to any geometry or design surface, and iii) efficient enough to cover the design space with a small number of design parameters.…”
Section: Surface Representation and Perturbationmentioning
confidence: 99%